MATEMÁTICA CONECTADA: UM STUDYGRAM COMO RECURSO DIDÁTICO PARA O ENSINO FUNDAMENTAL - Dutra, Elisangela Corrêa (2024)
The dissertation titled “Connected Mathematics: A Studygram as an Educational Resource for Elementary Education” falls within the “Teaching and Learning in Science and Mathematics” research line of the Professional Master’s Program in Science and Mathematics Education at Universidade Franciscana. This study primarily aimed to analyze the contributions of a digital social network-based educational resource for teaching and learning mathematics in the 9th grade. To this end, an educational product named “Calculelis” was developed, categorized as a Studygram - a term used for Instagram profiles focusing on educational content. The research was conducted in a public school in Santa Maria/RS, aiming to understand students’ perceptions of using the Studygram as a strategy to assist in learning mathematics. A mixed-methods approach was employed to analyze the data, utilizing both Descriptive Statistical Analysis and Implicative Statistical Analysis. The findings indicated significant positive acceptance amo